A case study of EFL students’ beliefs about English language learning - Do, Hieu Manh (Universitas Negeri Semarang, 2025)
Students’ beliefs about learning English play a crucial role in both learning and teaching. This study, therefore, examines Vietnamese EFL students’ beliefs about learning English across five different factors: self-efficacy, the roles of teachers and students, the nature of learning, and expectations. A total of 121 undergraduate students majoring in English from universities in Ho Chi Minh City were invited to complete an online survey via Google Forms. Their ratings were compared across the five belief areas, and independent T-tests were performed to identify any significant differences between male and female students' ratings. Results showed that students' perceptions of their own roles and self-efficacy were rated much higher than those of teachers, the learning process, and traditional learning expectations. Additionally, gender had little influence on beliefs about learning English. However, there was a significant difference in beliefs about self-efficacy and traditional learning orientation. Specifically, male students demonstrated higher confidence in their self-efficacy, while female students preferred traditional approaches more. The findings are discussed in terms of implications for teaching methods, especially the use of task-based language teaching and learner-centered instruction.